Prodromes, precipitants, and risk factors for relapse in bipolar disorder - Latalova, Klara; Prasko, Jan; Diveky, Tomas; Kamaradova, Dana; Grambal, Ales; Velartova, Hana (Neuro-endocrinology letters, 2012)
OBJECTIVE: The purpose of this qualitative review is to examine prodromes, precipitants, and risk factors for repeated episodes of mania and depression in bipolar disorder. METHODS: PubMed, EMBASE, and PsychInfo were searched for "bipolar disorder" in conjunction with: "prodromes", "triggers", and "life change events". RESULTS: Phenomenology and prevalence of prodromes, precipitants, and risk factors are described, and their therapeutic implications are outlined. CONCLUSIONS: Most patients with bipolar disorder are able to recognize their prodromes. This ability depends largely on insight. Psychoeducation focused on improving various aspects of insight, including treatment adherence, reduces incidence of relapses in bipolar disorder.
Keywords: recidiva; sekundární prevence; Prodromal Symptoms; Recurrence; antidepresiva; bipolární porucha; rizikové faktory; Antidepressive Agents; Humans; lidé; prodromální symptomy; Bipolar Disorder; incidence; Incidence; Secondary Prevention; Risk Factors